Pluralistic Ignorance in Concussion Reporting Among Student- Athletes. Issue 5 (31st May 2022) - Berkner, Paul D.; Driscoll, Haley T.; Marchetti, Gregory F.; Penna, Joseph W.; Ali, Humza; Jewell, Danielle E.; Herrmann, Lily
Background: The underreporting of concussions is a persistent problem among student athletes and has the potential to lead to negative health outcomes. The reasons for underreporting are multifactorial and included cultural norms and peer pressures of which one component is pluralistic ignorance. Purpose: To evaluate the impact of pluralistic ignorance on the decisions of concussion reporting amongst Division III athletes. We propose that gender, age, and type of sport will impact the responses that individuals make within a survey that they took in a group setting. Methods: A Qualtrics ® survey was created which contained an array of questions including; concussion knowledge, impulsivity, intention of self and teammate to report concussions and cultural reporting norms. The survey was administered in a group team setting and contained video vignettes depicting concussions and other injuries. The survey was administered to 295 NCAA Division III athletes representing 13 different sports: men's baseball, basketball, ice hockey, football, and women's field hockey, volleyball, soccer, softball, squash, and men's and women's Nordic skiing, lacrosse, rugby, ultimate frisbee. Results: 295 student athletes participated, 150 were women, 142 were men, 3 gender identified as other, and their ages ranged from 18 to 26. Individuals were excluded from the analysis if the individual responded inconsistently to both validator questions. Contact sport participants had higher scores on the knowledge questions and had increased agreement for teammate intention to report than their non-contact and collision counterparts (Kruskal-Wallis H = 9.61, P = .008) and had overall lower measures of impulsivity (H = 7.88, P = .019). Collision sport participants were less likely (59%) to endorse a teammate culture that was supportive of concussion reporting (C 2 = 13.56, P = .036) however female athletes (72%) and non-contact participants (79%) were more likely to endorse a culture supportive of self-reporting. Overall, regardless of gender, intention to play (self and teammate) despite concussion symptoms was endorsed by 66% of athletes and was more common among collision (75%) and contact participants (70%, C 2 = 12.14, P = .016). Conclusion: Despite the fact that the majority of college athletes don't endorse pluralistic ignorance within their teams (i.e. a cultural of not reporting) two-thirds of the college athletes still indicate they would not report their concussion symptoms.